Persepsi dan Dampak Eksistensi Indomaret Terhadap Warung Tradisional Di Kabupaten Halmahera Barat - Anita Dilly; Yuni Sara Raffane; Hendriane Namotemo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to determine the perception and impact of the existence of Indomaret on traditional stalls in West Halmahera Regency. This research is a qualitative research. The data in this study were obtained from research informants, namely traditional stall businesses in West Halmahera Regency who have businesses close to the existence of Indomaret. The results showed that the existence of Indomaret formed perceptions for traditional stall businesses and consumers, both negative and positive perceptions. The negative perception of traditional stall business actors occurs due to the impact caused by the existence of Indomaret, namely reduced customers and decreased income. On the other hand, the presence of Indomaret has a positive impact on traditional stall businesses in making it easier for them to meet their personal needs, stock up on goods, and to improve better service. The perception of the existence of Indomaret in the minds of consumers is formed through the price strategy offered by Indomaret so that it can determine consumer decisions to shop at Indomaret. Another impact of the existence of Indomaret on traditional stalls is seen in price competition, service, customers, income, as well as product variety and quality. Traditional stall businesses implement business strategies, namely selling more diverse products, selling retail products and improving service to customers to increase profits and attract customers.